Hubungan Lama Pengobatan Pasien TB Paru terhadap Rasio Monosit dan Limfosit (MLR) di Puskesmas - Sohibatul Islamiah; Ershandi Resnhaleksmana; Maruni Wiwiin Diarti; Urip Urip (Poltekkes Kemenkes Palembang, 2025)
Background: Tuberculosis (TB) is a chronic infectious disease caused by Mycobacterium tuberculosis, primarily affecting the lungs. TB treatment consists of two phases: intensive (initial) and continuation, which are carried out for a minimum of 6 months. One immunological indicator that can be used to monitor the response to TB therapy is the monocyte-to-lymphocyte ratio (MLR). Methods: This study used a quantitative approach with accidental sampling. The sample size was 30 pulmonary TB patients. Data were analyzed using the Spearman's Rho test. Results: Pulmonary TB patients were predominantly female (70%) and aged <46 years (83.3%). In the initial phase of treatment (months 1–2), the average monocyte count was 0.4, lymphocyte count 2.2, and MLR 0.20. In the continuation phase (months 3–6), the average monocyte count was 0.4, lymphocyte count 4.1, and MLR 0.1. Spearman's test results showed a significant relationship between treatment duration and MLR (r = -0.84; p = 0.000), with a negative correlation and very strong correlation. Conclusion: There is a significant relationship between the duration of pulmonary TB treatment and the MLR ratio, with the longer treatment duration tending to decrease.